The physiological basis of motor cortical oscillations in humans - Nowak, M (2017)
β- and γ-frequency oscillations are the dominant oscillatory activities in the human motor cortex (M1). However, their mechanisms and functional significance remain poorly understood. Controlled modulation of brain oscillations using transcranial alternating current stimulation (tACS) holds promise to advance this knowledge. The primary goal of this thesis was to investigate the neurophysiological mechanisms underlying β and γ oscillations. To this end, tACS was combined with transcranial magnetic stimulation (TMS; Chapters 4 and 5) and ultrahigh field (7T) Magnetic Resonance Spectroscopy (MRS; Chapter 6). Additionally, the relationship between MEG-measured oscillations and TMS-assessed physiological measures was examined (Chapter 7). The findings presented in Chapter 4 demonstrated that γ tACS led to a duration-dependent decrease in resting-state synaptic GABAA inhibition in M1; this effect was positively correlated with baseline GABAA decrease during movement preparation, when γ activity in motor circuitry is known to increase, suggesting that tACS may have similar physiological effects to endogenously driven local oscillatory activity. In addition, γ tACS-induced change in GABAA inhibition was closely related to performance in a motor learning task. Chapter 5 provided evidence on β tACS-induced modulation of corticospinal excitability (tACS phase-dependent) and extrasynaptic GABAA inhibition (tACS phase-independent) during movement preparation. Further, β tACS slowed down response time independently of its physiological effects. In Chapter 6, it was shown that β tACS reduced M1 GABA concentration; this change was dependent on the match between stimulation frequency and endogenous β-frequency, potentially reflecting a complex relationship between local tonic inhibitory activity and β oscillations. In contrast, no effect of β tACS on M1 glutamate levels was observed. Chapter 7 revealed an inverse relationship between endogenous β oscillatory power and movement-related corticospinal excitability. Moreover, peak frequency of movement-related γ synchronisation was related to performance in a motor learning task; local synaptic GABAA-mediated inhibition played an important role in this association. In conclusion, the results of the studies contained in this thesis offer a novel insight into the mechanistic basis of human motor cortical rhythms and provide evidence supporting the role of γ oscillations in motor learning, opening an interesting avenue for further research in the motor domain. Nevertheless, further study focused on addressing the limitations of tACS-based approaches is warranted.